Waste Heat Recovery and Energy Reutilization Technologies in Industrial Processes: Research on Improving Energy Efficiency and Reducing Emissions - Wang Yian (E3S Web of Conferences)
Industries are significant contributors to global energy consumption and greenhouse gas emissions, making energy efficiency improvements essential. WHR offers a valuable solution by capturing and reusing heat that would otherwise be lost, thus enhancing energy efficiency and reducing environmental impacts. This paper explores the application of WHR technologies across various industries, including steel, cement, and petrochemicals, where waste heat accounts for a large portion of energy losses. Technologies such as heat exchangers, ORC, and TEGs are discussed for their roles in converting waste heat into usable energy forms, such as electricity or heat for industrial processes. The review also covers advancements in materials and hybrid systems to optimize efficiency, as well as the potential of WHR in stabilizing renewable energy sources like solar and wind power. The integration of WHR systems into smart grids is highlighted as a future trend for improving energy management.